PENGARUH EDUKASI KETERAMPILAN BASIC LIFE SUPPORT MENGGUNAKAN VIDEO TERHADAP TINGKAT PENGETAHUAN DAN KETERAMPILAN MAHASISWA KEPERAWATAN MUHAMMADIYAH GORONTALO - Haslinda Damansyah; Pipin Yunus (-, 2021)
Basic Life Support (BLS) or in Indonesian known as Basic Life Assistance is an effort made to maintain life when the patient or victim experiences a life-threatening condition. Objective: to determine the influence of Basic Life Support of skills education on Knowledge level and Skills of Nursing Students. Method: The design of this research was Quasi Experiment with the One Group pre-post Test Design. The sample in this research were 61 respondents with collecting by used purposive sampling technique. Results: Based on the statistical tests  it has a significant value of 0,000 (p <0.05). Therefore Ho is rejected, meaning that there is a significant influence before and after given education used video. Conclusion: there is the effect of basic life support skills education used video on the knowledge level and skills of nursing students in Muhammadiyah university of Gorontalo.